Foot posture and landing error scores in recreational basketball players: a novel approach to prevent lower-limb injuries - Vinosh Kumar Purushothaman; Vinodhkumar Ramalingam; Mohand Khan; Arun Vijay Subbarayalu; Ambusam Subramaniam; Rajkumar Krishnan Vasanthi; Sivakumar Chinnusamy; Mohanraj Kandasmy; Palanivel Rubavathi Marimuthu (IP Iermakov S.S., 2023)
Background and Study Aim. Foot posture is an important determinant of a basketball player's performance. It influences their ability to generate power, maintain balance, and absorb shock. The aim of the current study was therefore to examine the association between foot posture and landing error score in recreational basketball players. Material and Methods. A cross-sectional study design was adopted. Fifty recreational basketball players from selected basketball clubs were chosen for the study. Their Foot Posture Index (FPI) and Landing Error Scores (LESS) were assessed. Nonparametric statistics, such as chi-square tests and the Mann-Whitney U test, were employed to examine the relationship between selected demographic variables and FPI and LESS scores. Additionally, assessed the difference in foot posture between the dominant and non-dominant legs. p-value less than 0.05 was considered significant. Results. Most participants exhibited normal foot posture, with no significant differences between the dominant and non-dominant legs, as assessed by FPI (p < 0.05). Additionally, an association was found between FPI and LESS scores, with 44% of participants showing a propensity for landing errors. The analysis revealed that a notable number of participants were categorized as 'poor' in LESS even with normal foot posture. This implies that landing errors are not only influenced by foot posture. Conclusions. There is an association between foot posture and the occurrence of landing errors in basketball players. This study emphasizes the need to thoroughly examine basketball players' FPI. It also underscores the importance of developing strategies aimed at helping them maintain optimal foot posture. These strategies can assist in avoiding landing errors, reducing the risk of injury, and promoting good health and well-being.